DAMPAK KEBIJAKAN HARGA DASAR PADA HARGA PRODUSEN, HARGA KONSUMEN DAN LUAS TANAM PADI: BELAJAR DARI PENGALAMAN MASA LALU - PRAJOGO U. HADI (SOCA: Jurnal Sosial Ekonomi Pertanian, 2006)
EFFECTS OF FLOOR PRICE POLICY ON PRODUCER AND CONSUMER PRICEAND AREA PLANTED OF RICE: LEARNING FROM THE PAST EXPERIENCES. Thegovernment has launched various policies so as to increase rice production, one of which wasfloor price for husked rice. From the results of the analysis employing regression methods andtime series data of 1969-1999, the following conclusions may be drawn. Firstly, the floor priceof husked rice tended to increase during the period under study. Secondly, a 10% increase in thefloor price of husked rice resulted in a 9,75% increase in the producer price; and a 10% increasein the producer price brought about a 8,39% increase in the consumer price of milled rice and a0,61% increase in area planted of rice. This indicates that an increase in the floor price directlyincreased the producer price and indirectly increased the consumer price and the area planted ofrice. Finally, the government policy successfully stabilised the domestic prices, and even theproducer price was more stable than the consumer prices. It is suggested that the floor pricepolicy needs to be continued with sufficient considerations of farmer’s profit and the world(Bangkok) price of milled rice.